A New 2D Echocardiographic Approach to Evaluate the Membrane and Valve Movement of the Berlin Heart EXCOR VAD Chamber in Pediatric VAD Patients. Issue 4 (17th April 2018) - Di Molfetta, Arianna; Iacobelli, Roberta; Ferrari, Gianfranco; Filippelli, Sergio; Perri, Gianluigi; Toscano, Alessandra; Adorisio, Rachele; Guccione, Paolo; Amodeo, Antonio
Abstract: The use of Berlin Heart EXCOR VAD (BH) is a validated therapy to bridge pediatric patients to heart transplant. Serial echocardiographic (ECHO) assessment of VAD patients is necessary to support patients' management. This work aims at developing an innovative strategy to evaluate the BH device functioning by ECHO and its interaction with the native heart in a pediatric population. ECHO evaluation of BH membrane movement, and inflow and outflow valves was performed in 2D, 2D‐color Doppler, M‐mode, and M‐mode color Doppler to assess the functioning of the device by direct positioning of the ECHO probe on the BH cannulas and membranes. Forty Berlin Heart EXCOR VAD were analyzed in 18 patients. Seven BH were placed as RVAD and 33 as LVAD. Results evidenced that 14 (21) inflow (outflow) valves presented a mild regurgitation, while 5 inflow (3 outflow) valves presented a moderate regurgitation. In three cases, we observed severe valve regurgitation with back flow in the left ventricle/right atrium. In both cases, the BH chambers were substituted, but we observed that in one case the regurgitation was due to cannulas compression, while in the other case it was due to valve malfunctioning. The M‐mode and the ECHO of the membranes and valves permitted to appreciate the beat phenomenon to assess if the native heart and the BH are working in opposite or in the same phase. The membrane ECHO permits evaluation of minimal changes in membrane movement to assure the completely empty‐completely fully work modality. Systematic ECHO assessment of BH chamber might support the BH programming and the detection of anomalous VAD‐heart interaction.